HIV Pre-exposure Prophylaxis and Its Impact on the Gut Microbiome in Men Having Sex With Men - Bragazzi, Nicola Luigi; Khamisy-Farah, Rola; Tsigalou, Christina; Mahroum, Naim (Frontiers in Microbiology, 2022)
HIV/AIDS still imposes a high epidemiological and societal burden. Together with antiretroviral therapy, pre-exposure prophylaxis (PrEP) represents a fundamental tool in the fight against HIV/AIDS. PrEP is considered effective and safe, even though it may affect organs like the kidney, bone, and liver, as shown by randomized clinical trials (RCTs). These side effects may be mediated by alterations of the gut microbiome. Whilst the impact of the human rectal and vaginal microbiome on HIV prevention has been highly investigated among women, less is known about its effect among men having sex with men (MSM), a vulnerable population at high risk for HIV and disproportionately affected by HIV/AIDS. In the present paper, we will overview the effects of PrEP on the gut microbiota in MSM. Mining PubMed/MEDLINE, we identified three studies that have found significant changes affecting the gut microbiota. However, these shifts in the gut microbiome composition are variable, probably due to methodological differences, even though all studies reviewed in the present overview consistently report aberrations at the level of the gut microbiota. More data are needed, especially concerning the long-term side effects of PrEP: despite the studies included being a high-quality RCT, and two well-designed cross-sectional studies, evidence related to the impact of HIV PrEP on the gut microbiome in MSM is scarce and based on small populations. A better understanding of the interactions between the gut microbiota, sexual orientation/identity, and HIV prevention is expected to improve PrEP adherence and devise strategies to counteract PrEP-related side effects.